Efektivitas Ekstrak Etanol Daun Durian (Durio zibethinus (Linn.)) sebagai Antihiperurisemia - Sonia, Rela; Yusnelti, Yusnelti; Fitrianingsih, Fitrianingsih (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2020)
Durian (Durio zibethinus Linn.) leaves are known to inhibit the xanthine oxidase enzyme which can reduce uric acid levels in the blood. The purpose of study is to determine the effectiveness of ethanol extracts of durian leaves in reducing uric acid levels in hyperuricemic mice. The mice were induced with chicken’s liver juice 0,2 mL/20 gBW and potassium oxonate 250 mg/kgBW. The animals were mice with uric acid levels above 3,3 mg/dL or 6,2-7,1 mg/dL. The study was used a completely randomized design (CRD) with six treatments and three replications, with three mice in each replications. The treatments group were K+: Allopurinol 10 mg/kgBW; K-: CMC-Na 0.5%; extracts in group P1,P2, P3, P4 are 50; 100; 200; 250 mg/kgBW. The measurements of uric acid levels were performed on day-0, day-6 after induction, and day-15 after administering each group. The data obtained were analyzed by One Way Anova test followed by Duncan's Post Hoc further test. The results showed that durian leaves could reduce uric acid levels in mice blood with the highest percentage reduction was in P2 (100 mg/kgBW) group of 40,53%, followed by P1 (50 mg/kgBW) of 38,68%. The lowest percentage was in the P4 group (250 mg/kgBW) of 22,36%, followed by the P3 group (200 mg/kgBW) of 27,71% and the ED50 value was 61,65 mg/kgBW. In conclusion, ethanol extracts of durian leaves has a significant effect on decreasing total uric acid levels in mice and has potential as an antihyperuricemia agent.